Performance of Primary Education in Burkina Faso : A Multi-Output Stochastic Frontier Analysis - Miningou, Elise Wendlassida; Vierstraete, Valerie (Taylor and Francis, 2018)
Primary education plays an important role in the development of human capital in developing countries. Consequently, Burkina Faso has taken steps to ensure both access to, and better quality of, primary education. However, comparisons between the different provinces of Burkina Faso reveal that there is a greater disparity between provinces in terms of access to, and the quality of, education, than there is in the provision of resources. Therefore, the objective of this study is to examine the efficiency of the resources used in providing primary education in Burkina Faso. We apply a stochastic frontier model in order to estimate the efficiency with which the 45 provinces of Burkina Faso provide primary education. The proposed model not only allows two outputs for primary education to be included, but also provides for an assessment of the factors that may affect inefficiency. Our results indicate that, overall, the primary education system in Burkina Faso operates at an efficiency level of approximately 63%. In addition, the living conditions of the population, as well as some factors internal to the education system, appear to have a relationship with the efficiency of primary education in the various provinces of Burkina Faso.